STUDI PENGOLAHAN BIJI BUAH NANGKA DALAM PEMBUATAN MINUMAN INSTAN - Mhd.Iqbal Nusa; Misril Fuadi; Siti Fatimah (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This research objectives was  to study the processing Nangka nut to produce Instant drinks.   This research used Completed Randomized Design Factorial with  two factors effect and two reflications. Thouse  effects  were level Natrium Metabisulfit  concentrations(N0 = 0%;, N1 = 0,1%;N2 = 0,2%; dan N3 = 0,3%), and level of adding  concentrations Maltodekstrin (M1= 4%;M2 = 6%; M3= 8%; dan ;M4= 10%) The results of the reasearch showed that Nangka fruit nut submerged in different concentration of Matabisulfit solutions did not cause the different significant effect to carbohydrate and Ash content of product. And other effect to Total Soluble Solid, Rendement, and Orgonoleptic value caushed the different significant effect.  The adding Maltodextrin at different concentrations did not cause the different significant effect to carbohydrate of product. Not other The adding Maltodextrin at different concentrations caused the different significant effect to Ash content, Total Soluble Solid (TSS), Rendement, and Organoleptic value of product Key word; Nangka fruit Nut, Metabisulfit Concentration, The adding Maltodextrin